Professionals’ perspectives on early intervention in Croatia: Comparing home - and - center based service quality - Škarica Burić, Ivana; Katušić, Ana (Specijalna edukacija i rehabilitacija, 2026)
Introduction. Early intervention (EI) services play a crucial role in supporting children at risk of developmental difficulties and their families. In Croatia, EI can be delivered either at home or in specialized centers, yet little is known about how professionals perceive the quality of these service models. Objectives. This study examined professionals’ perceptions of EI service quality, comparing home- and center-based provision, and explored whether perceptions varied according to professional experience, education, and frequency of service delivery. Methods. Sixty-seven professionals from across Croatia (91% female; median age = 32 years) participated. Median professional experience was 13 years, with 6 years in early intervention. Perceptions were assessed using an adapted Croatian version of the Inventory of Quality in Early Intervention Centres. Paired-samples t-tests compared home- and center-based ratings; regression analyses explored predictors of differences. Results: Overall quality ratings were significantly higher for home-based services (M = 3.9, SD = 0.54) than for center-based services (M = 3.6, SD = 0.30; p = .006, Cohen’s dz = 0.36). The largest differences favored home provision in child and family engagement, collaboration with families, and parental competences (all p < .001). Professional experience and postgraduate specialization were not significant predictors, whereas frequency of home-based provision was (B = 0.154, p= .037). Conclusion. Professionals perceived home-based early intervention as higher in quality, particularly in fostering collaboration and family engagement. Greater exposure to home-based practice enhanced recognition of its benefits, underscoring the need to expand family-centered, home-based early intervention services within Croatia’s social welfare system.
Keywords: early intervention; professional perceptions; service quality; family-centered practice